Physico-chemical caracterization of PM2.5 and PM10 collected in dry savanna of Banizoumbou in Niger and wet savanna of Djougou in Benin - AKPO, ARISTIDE BARTHÉLÉMY (My University, 2018)
Abstract This study, carried out in the context of climate change (greenhouse effect, rainfall acidity, atmospheric pollution), is part of the INDAAF (International Network to study Deposition and Atmospheric chemistry in Africa) program. It allowed the chemical characterization of the soluble part of fine particles whose diameter is less than 2.5 µm(PM2.5). and 10μm (PM10). These particles were collected in the dry savanna of Banizoumbou in Niger from 2005 to 2007 and in the wet savanna of Djougou in Benin from 2005 to 2009. Inorganic ions (Cl-, NO3-, SO42-, Na+, NH4+ , K+, Mg+, Ca2+) and organic (HCOO-, CH3COO-, C2H5COO-, C2O4-) were analyzed by ion chromatography. In Banizoumbou, high concentrations of Ca2+(0.91μg.m-3), NO3- (0.49μg.m-3) and SO42- ( 0.36 μg.m-3 ) were obtained in the dry season against 0.25, 0.65 and 0.18 respectively in the wet season. In Djougou, the most dominant ions are: Ca2+(0.59μg.m-3), NO3-(0.28 μg.m-3) and SO42- 0.16μg.m-3, respectively in the wet season.The NH4 concentration is not negligible in the wet season: 0.25μg.m-3 in Banizoumbou and 0.10 in Djougou. At the same time, the organic ions are the trace state. The results show that the atmosphere is more charged with particles in dry savanna than in wet savanna. Ca2+ and NH4 + have a strong capacity to neutralize rainwater in Banizoumbou during the wet season. In Djougou, only the NH4+ has significant effect as the concentration of SO42- increases due to phytoplankton activity. These findings partly explain the alkaline character of the rains at Banizoumbou and acid at Djougou. The neutralization process involves oxidation, heterogeneous nucleation, condensation and coagulation of fine particles
Keywords: Fine particles; physicochemical processes; neutralization; nucleation; condensation; coagulation.